Kabar Baik di Sumur Sikhar - Darmanto D (Sekolah Tinggi Theologia Nazarene Indonesia, 2019)
In the world of missiology, there is a wide range of methods and approaches to preach the good news (Gospel); from time to time the experts tried to make the methods and strategies to respond to the needs of the proclamation of the good news in accordance with the time. Jesus ' conversation with the Samaritan woman by nature on the banks of Jacob's well in town Sikhar, remains the inspiration that no fission by age, because the principles that Jesus used can still be applied as a method and strategy of delivering good news at the present time